2017
DOI: 10.1074/jbc.m116.749804
|View full text |Cite
|
Sign up to set email alerts
|

CD6 Receptor Regulates Intestinal Ischemia/Reperfusion-induced Injury by Modulating Natural IgM-producing B1a Cell Self-renewal

Abstract: Edited by Luke O'NeillIntestinal ischemia/reperfusion (I/R) injury is a relatively common pathological condition that can lead to multi-organ failure and mortality. Regulatory mechanism for this disease is poorly understood, although it is established that circulating pathogenic natural IgM, which is primarily produced by B1a cells outside of the peritoneal cavity, are integrally involved. CD6 was originally identified as a marker for T cells and was later found to be present on some subsets of B cells in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
3
19
1
Order By: Relevance
“…Our latest studies of B cells in CD6 KO mice showed that, unlike in humans, CD6 is not expressed on any of the B2 cells (specifically marginal and follicular B cells) in mice, neither constitutively nor after activation (33). Instead, mouse CD6 is selectively expressed on a small subset of B1a cells found in the spleen, liver, and peripheral blood, but not in the bone marrow or peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Our latest studies of B cells in CD6 KO mice showed that, unlike in humans, CD6 is not expressed on any of the B2 cells (specifically marginal and follicular B cells) in mice, neither constitutively nor after activation (33). Instead, mouse CD6 is selectively expressed on a small subset of B1a cells found in the spleen, liver, and peripheral blood, but not in the bone marrow or peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…To provide additional evidence that might help us establish to what extent this hypothesis can be confirmed, we identified in rainbow trout (Oncorhynchus mykiss) a homolog of CD5 and demonstrated that a major fraction of trout splenic B cells express CD5 on the cell surface. Additionally, we identified a homolog of CD6, another member of the SRCR family of receptors recently described to be selectively expressed on mammalian splenic B1a cells (30) and T cells (31), demonstrating that fish B cells also transcribe CD6. Further phenotypical and functional characterization of fish B cells in parallel to murine splenic B2 cells clearly established a resemblance of fish IgM + B cell responses to mammalian B1 cell responses regardless of CD5 surface expression.…”
mentioning
confidence: 82%
“…Intestinal ischaemia/reperfusion (II/R) injury is closely related to mesenteric ischaemia, haemorrhagic shock, and organ transplantation (Enyindah‐Asonye et al, ; X. H. Liu et al, ; Matsuo, Chaung, Liou, Wang, & Yang, ; W. Zhou et al, ). Intestinal ischaemia can cause cell damage and provoke epithelial barrier dysfunction during reperfusion, resulting in systemic inflammatory response syndrome (SIRS), multiple organ dysfunction syndrome (MODS), and death (Duranti et al, ; Feng et al, ; Impellizzeri et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal ischaemia/reperfusion (II/R) injury is closely related to mesenteric ischaemia, haemorrhagic shock, and organ transplantation (Enyindah-Asonye et al, 2017;X. H. Liu et al, 2015;Matsuo, Chaung, Liou, Wang, & Yang, 2018;W.…”
Section: Introductionmentioning
confidence: 99%